2005
DOI: 10.1074/jbc.m500391200
|View full text |Cite
|
Sign up to set email alerts
|

MxA, a Member of the Dynamin Superfamily, Interacts with the Ankyrin-like Repeat Domain of TRPC

Abstract: Mammalian transient receptor potential canonical channels have been proposed as the molecular entities associated with calcium entry activity in nonexcitable cells. Amino acid sequence analyses of TRPCs revealed the presence of ankyrin-like repeat domains, one of the most common protein-protein interaction motifs. Using a yeast two-hybrid interaction assay, we found that the second ankyrin-like repeat domain of TRPC6 interacted with MxA, a member of the dynamin superfamily. Using a GST pull-down and co-immunop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 69 publications
1
37
0
Order By: Relevance
“…Exocytosis of the TRPC6 channel to the cell surface is a known requirement for channel activity (65). We showed that knockdown of PTEN impaired TRPC6 localization at the cell membrane.…”
Section: Discussionmentioning
confidence: 79%
“…Exocytosis of the TRPC6 channel to the cell surface is a known requirement for channel activity (65). We showed that knockdown of PTEN impaired TRPC6 localization at the cell membrane.…”
Section: Discussionmentioning
confidence: 79%
“…MxA [54] MxA [54] MxA [54] MxA [54] MxA [54] MxA [54] MxA [54] RhoA [57] RhoA RhoA SNARES [89] SNARES [95] SNARES [8,26] Only proteins common to 2 or more TRPCs have been listed. Components involved in Ca 2+ signaling are shown in the top half of the PMCA [38,39,50] Caveolin [1,13,51] STIM1 [32,52,72] SERCA [50,38,39] proteins involved in vesicle trafficking, cytoskeletal interactions, and scaffolding (see Table 2).…”
Section: Role Of Trpc-cation Channels In Agonist-stimulated Ca 2+ Entrymentioning
confidence: 99%
“…MxA, a member of the dynamin superfamily [54], and this interaction is most likely involved in trafficking of the channel. However, the exact components of the TRPC3 channelosome that are involved in constitutive and regulated trafficking of TRPC3, as well as its ability to generate SOC channels, have not yet been resolved.…”
Section: Ca 2+mentioning
confidence: 99%
“…Colonies were analyzed by quantitative ␤-galactosidase (␤-Gal) liquid assay, according to the Clontech protocol. Expression of the constructs used for the ␤-Gal liquid assay was confirmed by yeast protein extraction as described previously (27).…”
Section: Methodsmentioning
confidence: 99%